Valorization of Reground Pasta By-Product through PHA Production with Phototrophic Purple Bacteria - Marchetti, Angela (2024)
Funding Information: The JU receives support from the European Union’s Horizon 2020 research and innovation program and the Bio-based Industries Consortium. M.P. acknowledges the financial support of FCT (Fundação para a Ciência e a Tecnologia) through the Ph.D. grant DFA/BD/05659/2020. Publisher Copyright: © 2024 by the authors.